Progress or regress on gender equality: The case study of selected transport STEM careers and their vocational education and training in Japan. (June 2019) - Kitada, Momoko; Harada, Junko
Abstract: This paper examines the role of vocational education and training (VET) in the STEM workforce to advance women's integration into traditionally male-dominated workplaces. In Japan, it has been reported that the size of the workforce has been substantially decreasing since 2011. One of the effective strategies to mitigate the risk of the shortage of human resources is considered to be making use of women in the STEM field. In this paper, the Japanese transport sector is studied to understand the role of VET to support women in the STEM workforce. We shed light on the merchant marine as one of the most male-dominated industries. A comparative institutional analysis was elaborated with other transport industries, such as air and rail. In addition, a narrative analysis was conducted with the empirical data as well as archived literature. The paper reveals that the merchant marine has failed to establish an institutional arrangement of maritime VET from the women transport workers' career-cycle perspective. The paper concludes that the role of VET is important not only before the employment but also after, in order to make sustainable use of women as human resources. In order to remove barriers to including women in STEM careers, institutional arrangement of VET should be reviewed through gender-mainstreaming and life-long VET would help to stop the leaky pipe line of STEM women in Japan. Highlights: The first comparative gender study of Japanese transport industries. A life-long learning support appeared to be effective to support women's career development in air and rail industries in Japan. Japan's low public expenditure in training and institutional arrangement, preventing women from STEM fields. Institutional arrangement of maritime VET should be reviewed through gender-mainstreaming to eliminate the systematic problems of excluding women seafarers from training opportunities.